Students’ problem-solving ability in solving algebra tasks using the context of Palembang - Ratu Ilma Indra Putri; Zulkardi; Arini Dyah Riskanita (Journal on Mathematics Education, 2022)
This descriptive research aimed to know students' problem-solving ability in arithmetic operations on algebra forms through an Indonesian realistic mathematics education, namely Pendidikan Matematika Realistik Indonesia (PMRI), approach in secondary school number 17 Palembang. The learning process, material, and assessment used were principles and characteristics of PMRI. The data collection technique was done by two students' activities and the written test to measure students' problem-solving abilities. The written test, which referred to the indicators of problem-solving ability, was given after the learning process. This study's findings indicate that Palembang's context helps students comprehend algebraic arithmetic operations. The principles and characteristics of PMRI play an essential role in enhancing students' problem-solving skills. To conclude, students develop and solve problems by modeling based on their mathematical ideas. In addition, students must be able to develop problem-solving strategies in which they employ a variety of procedures.